Antibacterial plastic as well as preparation method and application thereof
By adding functionalized polylactic acid and graphene oxide to the antibacterial plastic formula to generate silica and loading silver nanoparticles, the problem of poor moisture-proof performance of antibacterial plastics is solved, and higher mechanical properties and moisture-proof performance are achieved, and suitable for moisture-proof food packaging.
Patent Information
- Application Number
- CN202510346056.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Antibacterial plastics have poor moisture resistance when used in food packaging, resulting in food spoilage.
Using an antibacterial plastic, the formulation includes polylactic acid, functionalized polylactic acid, antioxidant and plasticizer, the mechanical properties, antibacterial properties and moisture-proof properties of the material are enhanced by generating silica in situ on the surface of graphene oxide and loading silver nanoparticles.
It significantly improves the mechanical properties and moisture-proof properties of antibacterial plastics, can effectively prevent food from deteriorating, and is suitable for packaging of moisture-proof foods.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polylactic acid materials, and in particular to an antibacterial plastic and a preparation method and application thereof. Background Art
[0002] Polylactic acid (PLA), a fully biodegradable polyester derived from renewable resources, is considered to be the most promising material on the market due to its good biocompatibility, biodegradability, mechanical properties and transparency. It is widely used in industries such as food packaging and healthcare.
[0003] Patent technical document CN116622205A discloses a method for preparing a polylactic acid antibacterial plastic. The invention reduces silver nitrate in situ in a chitosan solution to prepare a silver-loaded chitosan antibacterial agent; PLA is used as a matrix material, chitosan is added, and polylactic acid-chitosan antibacterial plastic is prepared through solution blending, melt blending, tableting and injection molding; or PLA is used as a matrix material, a silver-loaded chitosan antibacterial agent is added, and polylactic acid-silver-loaded chitosan antibacterial plastic is prepared through solution blending, melt blending, tableting and injection molding, which has good antibacterial properties.
[0004] Patent technical document CN115418051A discloses a biodegradable antibacterial plastic masterbatch, a preparation method thereof and an antibacterial plastic product containing the same. The biodegradable antibacterial plastic masterbatch comprises polypropylene plastic masterbatch, polylactic acid plastic masterbatch, antibacterial powder and an antioxidant; the antibacterial powder comprises an antibacterial colloid and a filler; the antibacterial colloid comprises anthocyanin-modified nano-gold particles, and the antibacterial plastic has good antibacterial properties and biodegradability.
[0005] However, when plastic is used for some foods that are easily humid, such as biscuits, tea, etc., it often causes the food to spoil due to the poor moisture-proof performance of plastic. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide an antibacterial plastic and a preparation method and application thereof, so as to solve the problem that the antibacterial plastic has poor moisture-proof performance when used for food packaging.
[0007] Based on the above purpose, the present invention provides an antibacterial plastic, comprising the following raw materials in parts by weight: 60-90 parts of polylactic acid, 10-15 parts of functionalized polylactic acid, 1-2 parts of antioxidant, and 1-3 parts of plasticizer; The preparation steps of the functionalized polylactic acid are as follows: S1: dissolving ethyl orthosilicate in an ethanol solution, adjusting the pH to 3.7-4.2, stirring evenly to obtain a silane solution, dispersing graphene oxide in the ethanol solution, and obtaining a graphene oxide solution after ultrasonic treatment, and then mixing the two, adjusting the pH to 8.5-9 after ultrasonic treatment, and then stirring at 60-70°C for 1-2h. After the reaction is completed, centrifuging, washing, and drying to obtain graphene oxide loaded with silicon dioxide; The usage ratio of ethyl orthosilicate and graphene oxide in step S1 is 100-300g:2-3g.
[0008] S2: heating silver nitrate to boiling, then adding sodium citrate solution, cooling the solution to room temperature after it turns yellow, centrifuging to obtain colloidal silver nanoparticles; adding the colloidal silver nanoparticles to silica-loaded graphene oxide, ultrasonically treating for 15-20 minutes, and drying to obtain functionalized graphene oxide; The usage ratio of the silver nitrate and sodium citrate solutions in step S2 is 80-100 mL:8-10 mL.
[0009] The usage ratio of the colloidal silver nanoparticles and the silicon dioxide-loaded graphene oxide in step S2 is 80-100 ml: 2-3 g.
[0010] S3: In a nitrogen atmosphere, pentaerythritol, PLLA, isophorone diisocyanate, dibutyltin dilaurate and N,N-dimethylformamide are mixed and reacted for 2-3 hours, and then functionalized graphene oxide is added to react for 8-10 hours, and finally dried at 80°C for 24 hours and crushed to obtain functionalized polylactic acid; The usage ratio of pentaerythritol, PLLA, isophorone diisocyanate, dibutyltin dilaurate, N,N-dimethylformamide and functionalized graphene oxide in step S3 is 4.25-5g:5-10g:2-3g:0.01-0.05g:40-60ml:1-2g; Preferably, the pH is adjusted to 3.7-4.2 in step S1 using acetic acid.
[0011] Preferably, the pH value in step S1 is adjusted to 8.5-9 by using sodium hydroxide.
[0012] Preferably, the ethanol solution in step S1 is a mixture of ethanol and deionized water in a volume ratio of 4:1.
[0013] Preferably, the centrifugation in step S1 is performed at 8000 rpm.
[0014] Preferably, the concentration of silver nitrate in step S2 is 0.001 M.
[0015] Preferably, the graphene oxide in step S1 is in the form of a single-layer sheet or a layered structure of a small number of stacked sheets.
[0016] Preferably, the concentration of the sodium citrate solution in step S2 is 1%.
[0017] Preferably, the centrifugation in step S2 is performed at 9000-10000 rpm for 10 min.
[0018] Preferably, the drying in step S3 is performed at 80° C. for 24 hours.
[0019] Preferably, the weight average molecular weight of the polylactic acid is 60,000-150,000.
[0020] Preferably, the plasticizer is a mixture of polyethylene glycol and chitosan solution in a weight ratio of 5:3.
[0021] Preferably, the antioxidant is one of N,N'-di-(1-methylheptyl)-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline and 2,6-di-tert-butyl-4-methylphenol.
[0022] Furthermore, the present invention also provides a method for preparing an antibacterial plastic, the specific steps of which are as follows: (1) Polylactic acid, functionalized polylactic acid and antioxidant are mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (2) Add the masterbatch into an extruder, then add a plasticizer, and control the temperature of the extruder between 140-240°C to obtain composite particles; (3) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0023] Furthermore, the present invention also provides an application of the antibacterial plastic for packaging moisture-proof food.
[0024] Beneficial effects of the present invention: When preparing functionalized polylactic acid, the antibacterial plastic of the present invention increases the cross-linking density of the polymer by adding pentaerythritol, so that the mechanical properties and moisture-proof properties of the antibacterial plastic are significantly improved.
[0025] The antibacterial plastic of the present invention avoids the occurrence of agglomeration caused by excessive addition of inorganic particles by in-situ growing silicon dioxide on the surface of graphene oxide and loading silver nanoparticles, while improving the density of graphene oxide, so that the antibacterial property, mechanical property and moisture-proof property of the antibacterial plastic are further improved.
[0026] The antibacterial plastic of the present invention further improves the antibacterial and moisture-proof properties of the antibacterial plastic by adding functionalized graphene oxide after preparing the functionalized polylactic acid, so that the functionalized graphene oxide is on the side chain of the functionalized polylactic acid and has a certain activity. DETAILED DESCRIPTION
[0027] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0028] Embodiment 1: An antibacterial plastic, the preparation method is as follows: (1) Dissolve 100 g of tetraethyl orthosilicate in 1 L of ethanol solution, add acetic acid to adjust the pH to 3.7, stir evenly to obtain a silane solution, disperse 2 g of graphene oxide in 300 mL of ethanol solution, and obtain a graphene oxide solution after ultrasonic treatment. Then mix the two, and after ultrasonic treatment, add sodium hydroxide to adjust the pH to 8.5. Then stir at 60°C for 1 h. After the reaction is completed, centrifuge at 8000 rpm and wash with ethanol. Finally, dry in an oven at 50°C for 24 h to obtain graphene oxide loaded with silica. (2) 80 mL of silver nitrate was heated to boiling, and then 8 mL of 1% sodium citrate solution was added. After the solution turned yellow, it was cooled to room temperature and then centrifuged at 9000 rpm for 10 min to obtain colloidal silver nanoparticles; 80 ml of colloidal silver nanoparticles were added to 2 g of silica-loaded graphene oxide, ultrasonically treated for 15 min, and dried to obtain functionalized graphene oxide; (3) In a nitrogen atmosphere, 4.25 g of pentaerythritol, 5 g of PLLA, 2 g of isophorone diisocyanate, 0.01 g of dibutyltin dilaurate and 40-60 ml of N,N-dimethylformamide were mixed and reacted for 2 h, and then 1 g of functionalized graphene oxide was added and reacted for 8 h. Finally, the mixture was dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid. (4) 60 g of polylactic acid, 10 g of functionalized polylactic acid and 1 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (5) adding the masterbatch into an extruder, and then adding 1 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 140° C. to obtain composite particles; (6) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0029] Embodiment 2: An antibacterial plastic, the preparation method is as follows: (1) Dissolve 200 g of tetraethyl orthosilicate in 1 L of ethanol solution, add acetic acid to adjust the pH to 4, stir evenly to obtain a silane solution, disperse 2.5 g of graphene oxide in 400 mL of ethanol solution, and obtain a graphene oxide solution after ultrasonic treatment. Then mix the two, and after ultrasonic treatment, add sodium hydroxide to adjust the pH to 8.8, then stir at 65 ° C for 2 h. After the reaction is completed, centrifuge at 8000 rpm and wash with ethanol, and finally dry in an oven at 50 ° C for 24 h to obtain graphene oxide loaded with silicon dioxide; (2) 90 mL of silver nitrate was heated to boiling, and then 9 mL of 1% sodium citrate solution was added. After the solution turned yellow, it was cooled to room temperature and then centrifuged at 9500 rpm for 10 min to obtain colloidal silver nanoparticles; 90 ml of colloidal silver nanoparticles were added to 2.5 g of silica-loaded graphene oxide, ultrasonically treated for 18 min, and dried to obtain functionalized graphene oxide; (3) In a nitrogen atmosphere, 4.75 g of pentaerythritol, 8 g of PLLA, 2.5 g of isophorone diisocyanate, 0.03 g of dibutyltin dilaurate and 50 ml of N,N-dimethylformamide were mixed and reacted for 3 h. Then, 1.5 g of functionalized graphene oxide was added and reacted for 9 h. Finally, the mixture was dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid. (4) 75 g of polylactic acid, 13 g of functionalized polylactic acid and 1.5 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (5) adding the masterbatch into an extruder, and then adding 2 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 180° C. to obtain composite particles; (6) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0030] Embodiment 3: An antibacterial plastic, the preparation method is as follows: (1) Dissolve 300 g of tetraethyl orthosilicate in 1 L of ethanol solution, add acetic acid to adjust the pH to 4.2, stir evenly to obtain a silane solution, disperse 3 g of graphene oxide in 500 mL of ethanol solution, and obtain a graphene oxide solution after ultrasonic treatment. Then mix the two, and after ultrasonic treatment, add sodium hydroxide to adjust the pH to 9. Then stir at 70 ° C for 2 h. After the reaction is completed, centrifuge at 8000 rpm and wash with ethanol. Finally, dry in an oven at 50 ° C for 24 h to obtain graphene oxide loaded with silica; (2) 100 mL of silver nitrate was heated to boiling, and then 10 mL of 1% sodium citrate solution was added. After the solution turned yellow, it was cooled to room temperature and then centrifuged at 10,000 rpm for 10 min to obtain colloidal silver nanoparticles; 100 ml of colloidal silver nanoparticles was added to 3 g of silica-loaded graphene oxide, ultrasonically treated for 20 min, and dried to obtain functionalized graphene oxide; (3) In a nitrogen atmosphere, 5 g of pentaerythritol, 10 g of PLLA, 3 g of isophorone diisocyanate, 0.05 g of dibutyltin dilaurate and 60 ml of N,N-dimethylformamide were mixed and reacted for 3 h. Then, 2 g of functionalized graphene oxide was added and reacted for 10 h. Finally, the mixture was dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid. (4) 90 g of polylactic acid, 15 g of functionalized polylactic acid and 2 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (5) adding the masterbatch into an extruder, and then adding 3 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 240 °C to obtain composite particles; (6) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0031] Comparative Example 1: An antibacterial plastic, the preparation method is as follows: (1) Dissolve 200 g of tetraethyl orthosilicate in 1 L of ethanol solution, add acetic acid to adjust the pH to 4, stir evenly to obtain a silane solution, disperse 2.5 g of graphene oxide in 400 mL of ethanol solution, and obtain a graphene oxide solution after ultrasonic treatment. Then mix the two, and after ultrasonic treatment, add sodium hydroxide to adjust the pH to 8.8, then stir at 65 ° C for 2 h. After the reaction is completed, centrifuge at 8000 rpm and wash with ethanol, and finally dry in an oven at 50 ° C for 24 h to obtain graphene oxide loaded with silicon dioxide; (2) 90 mL of silver nitrate was heated to boiling, and then 9 mL of 1% sodium citrate solution was added. After the solution turned yellow, it was cooled to room temperature and then centrifuged at 9500 rpm for 10 min to obtain colloidal silver nanoparticles; 90 ml of colloidal silver nanoparticles were added to 2.5 g of silica-loaded graphene oxide, ultrasonically treated for 18 min, and dried to obtain functionalized graphene oxide; (3) In a nitrogen atmosphere, 4.75 g of ethylene glycol, 8 g of PLLA, 2.5 g of isophorone diisocyanate, 0.03 g of dibutyltin dilaurate and 50 ml of N,N-dimethylformamide were mixed and reacted for 3 h. Then, 1.5 g of functionalized graphene oxide was added and reacted for 9 h. Finally, the mixture was dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid. (4) 75 g of polylactic acid, 13 g of functionalized polylactic acid and 1.5 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (5) adding the masterbatch into an extruder, and then adding 2 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 180° C. to obtain composite particles; (6) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0032] Comparative Example 2: An antibacterial plastic, the preparation method is as follows: (1) 90 mL of silver nitrate was heated to boiling, and then 9 mL of 1% sodium citrate solution was added. After the solution turned yellow, it was cooled to room temperature and then centrifuged at 9500 rpm for 10 min to obtain colloidal silver nanoparticles; 90 ml of colloidal silver nanoparticles were added to 2.5 g of graphene oxide, ultrasonically treated for 18 min, and dried to obtain functionalized graphene oxide; (2) In a nitrogen atmosphere, 4.75 g of pentaerythritol, 8 g of PLLA, 2.5 g of isophorone diisocyanate, 0.03 g of dibutyltin dilaurate and 50 ml of N,N-dimethylformamide were mixed and reacted for 3 h. Then, 1.5 g of functionalized graphene oxide was added and reacted for 9 h. Finally, the mixture was dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid. (3) 75 g of polylactic acid, 13 g of functionalized polylactic acid and 1.5 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (4) adding the masterbatch into an extruder, and then adding 2 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 180° C. to obtain composite particles; (5) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0033] Comparative Example 3: An antibacterial plastic, the preparation method is as follows: (1) Dissolve 200 g of tetraethyl orthosilicate in 1 L of ethanol solution, add acetic acid to adjust the pH to 4, stir evenly to obtain a silane solution, disperse 2.5 g of graphene oxide in 400 mL of ethanol solution, and obtain a graphene oxide solution after ultrasonic treatment. Then mix the two, and after ultrasonic treatment, add sodium hydroxide to adjust the pH to 8.8, then stir at 65 ° C for 2 h. After the reaction is completed, centrifuge at 8000 rpm and wash with ethanol, and finally dry in an oven at 50 ° C for 24 h to obtain graphene oxide loaded with silicon dioxide; (2) In a nitrogen atmosphere, 4.75 g of pentaerythritol, 8 g of PLLA, 2.5 g of isophorone diisocyanate, 0.03 g of dibutyltin dilaurate and 50 ml of N,N-dimethylformamide were mixed and reacted for 3 h. Then, 1.5 g of silica-loaded graphene oxide was added and reacted for 9 h. Finally, the mixture was dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid. (3) 75 g of polylactic acid, 13 g of functionalized polylactic acid and 1.5 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (4) adding the masterbatch into an extruder, and then adding 2 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 180° C. to obtain composite particles; (5) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0034] Comparative Example 4: An antibacterial plastic, the preparation method is as follows: (1) Dissolve 200 g of tetraethyl orthosilicate in 1 L of ethanol solution, add acetic acid to adjust the pH to 4, stir evenly to obtain a silane solution, disperse 2.5 g of graphene oxide in 400 mL of ethanol solution, and obtain a graphene oxide solution after ultrasonic treatment. Then mix the two, and after ultrasonic treatment, add sodium hydroxide to adjust the pH to 8.8, then stir at 65 ° C for 2 h. After the reaction is completed, centrifuge at 8000 rpm and wash with ethanol, and finally dry in an oven at 50 ° C for 24 h to obtain graphene oxide loaded with silicon dioxide; (2) 90 mL of silver nitrate was heated to boiling, and then 9 mL of 1% sodium citrate solution was added. After the solution turned yellow, it was cooled to room temperature and then centrifuged at 9500 rpm for 10 min to obtain colloidal silver nanoparticles; 90 ml of colloidal silver nanoparticles were added to 2.5 g of silica-loaded graphene oxide, ultrasonically treated for 18 min, and dried to obtain functionalized graphene oxide; (3) In a nitrogen atmosphere, 4.75 g of pentaerythritol, 8 g of PLLA, 2.5 g of isophorone diisocyanate, 0.03 g of dibutyltin dilaurate and 50 ml of N,N-dimethylformamide were mixed, and 1.5 g of functionalized graphene oxide was added to react for 3 h, and then dried at 80 °C for 24 h and crushed to obtain functionalized polylactic acid; (4) 75 g of polylactic acid, 13 g of functionalized polylactic acid and 1.5 g of N,N'-di-(1-methylheptyl)-p-phenylenediamine were mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (5) adding the masterbatch into an extruder, and then adding 2 g of a mixture of polyethylene glycol and chitosan solution, and controlling the temperature of the extruder at 180° C. to obtain composite particles; (6) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
[0035] Performance Testing: Tensile strength: The test was carried out using an AI-7000S tensile testing machine. The tensile test was carried out at a constant speed of 50 mm / min at room temperature. The test results are shown in Table 1. Light transmittance: The obtained samples were cut into squares (5 cm × 5 cm) and tested using a UV-visible spectrophotometer. The test results are shown in Table 1. Antibacterial properties: The antibacterial properties of the obtained samples were tested with two pathogenic bacteria, Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus. The test results are shown in Table 1; Moisture-proof performance test: The test was conducted through a packaging experiment. The tough biscuits of the same mass were packed into glass sample bottles. The bottle mouths were sealed with the samples obtained in the embodiment and the comparative example respectively. The packaged biscuits were stored at room temperature for 10 days. Without taking out the biscuit samples, the packages were weighed and recorded at a fixed time every day. The mass change rate of the biscuits was calculated as follows:
[0036] Where, M is the weight of the initial biscuit; M0 is the weight of the biscuits after 10 days.
[0037] Table 1 Performance test results Tensile strength (MPa) Light transmittance (%) Antibacterial rate / Escherichia coli (%) Antibacterial rate / Staphylococcus aureus (%) Quality change rate (%) Example 1 10.97 95.3 98.8 98.7 0.91 Example 2 12.40 95.6 99.2 98.2 0.84 Example 3 12.13 94.7 98.4 98.6 0.88 Comparative Example 1 9.74 96.2 98.7 98.1 4.56 Comparative Example 2 10.23 95.4 94.5 94.7 5.47 Comparative Example 3 11.41 96.2 93.4 93.2 4.37 Comparative Example 4 12.57 93.6 95.3 95.4 6.58 Data analysis: The antibacterial plastic of the present invention has excellent mechanical and optical properties, and has excellent inhibitory properties against Gram-negative bacteria Escherichia coli and Gram-positive bacteria Staphylococcus aureus. Most importantly, when it is used in the packaging experiment of tough biscuits, the quality of the biscuits remains basically unchanged after 10 days, and it can be widely used in moisture-proof food packaging.
[0038] It can be seen from the data of Example 1 and Comparative Example 1 in Table 1 that when preparing functionalized polylactic acid, the mechanical properties and moisture-proof properties of the antibacterial plastic are significantly improved by adding pentaerythritol. This is mainly because pentaerythritol, as a multifunctional alcohol, can increase the cross-linking density and form a cross-linking network, thereby improving the mechanical properties and moisture-proof properties of the polymer. At the same time, in the subsequent melt extrusion process, the matrix polylactic acid can be interspersed in the cross-linking network of the functionalized polylactic acid, further improving the mechanical strength and moisture-proof properties of the polymer.
[0039] It can be seen from the data of Example 1 and Comparative Example 2 in Table 1 that the in-situ generation of silicon dioxide on the surface of graphene oxide can improve the mechanical properties, antibacterial properties and moisture-proof properties of the antibacterial plastic to a certain extent. This is mainly because the in-situ generated silicon dioxide can be embedded in the graphene oxide lamellae, expanding the lamellae space, which not only weakens the interaction force between the graphene oxide lamellae, making the graphene oxide more evenly dispersed, but also makes the graphene oxide easier to kill bacteria; on the other hand, compared with directly adding silicon dioxide and graphene oxide, it avoids the occurrence of agglomeration caused by the addition of too many inorganic particles. At the same time, the in-situ growth allows silicon dioxide to form a dense layer on the surface of graphene oxide, which more effectively prevents the entry of moisture.
[0040] It can be seen from the data of Example 1 and Comparative Example 3 in Table 1 that silver nanoparticles are loaded on the surface of graphene oxide, while ensuring the addition of antibacterial particles, the occurrence of agglomeration caused by excessive addition of inorganic particles is avoided. In addition, graphene has a large specific surface area and good electrical conductivity. Using it as a carrier can not only promote the antibacterial activity of silver nanoparticles but also enhance the contact efficiency between silver nanoparticles and bacterial cell membranes, thereby improving the bactericidal effect. In addition, the loading of silver can further increase the density and prevent the penetration of water.
[0041] It can be seen from the data of Example 1 and Comparative Example 4 in Table 1 that when preparing the functionalized polylactic acid, the functionalized graphene oxide is added later, so that the antibacterial and moisture-proof properties of the antibacterial plastic are further improved. This may be because the functionalized graphene oxide is on the side chain of the functionalized polylactic acid, has a certain activity, and can kill bacteria in a larger range. At the same time, the functionalized graphene oxide on the side chain can stack with each other to further form a physical barrier to hinder the penetration of moisture.
[0042] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. An antibacterial plastic, characterized in that: The composition comprises the following raw materials in parts by weight: 60-90 parts of polylactic acid, 10-15 parts of functionalized polylactic acid, 1-2 parts of antioxidant, and 1-3 parts of plasticizer; The preparation steps of the functionalized polylactic acid are as follows: S1: dissolving ethyl orthosilicate in an ethanol solution, adjusting the pH to 3.7-4.2, stirring evenly to obtain a silane solution, dispersing graphene oxide in the ethanol solution, and obtaining a graphene oxide solution after ultrasonic treatment, and then mixing the two, adjusting the pH to 8.5-9 after ultrasonic treatment, and then stirring at 60-70°C for 1-2h. After the reaction is completed, centrifuging, washing, and drying to obtain graphene oxide loaded with silicon dioxide; The usage ratio of ethyl orthosilicate and graphene oxide in step S1 is 100-300 g:2-3 g; S2: heating silver nitrate to boiling, then adding sodium citrate solution, cooling the solution to room temperature after it turns yellow, centrifuging to obtain colloidal silver nanoparticles; adding the colloidal silver nanoparticles to silica-loaded graphene oxide, ultrasonically treating for 15-20 minutes, and drying to obtain functionalized graphene oxide; The usage ratio of the silver nitrate and sodium citrate solutions in step S2 is 80-100 mL:8-10 mL; The amount ratio of the colloidal silver nanoparticles to the silicon dioxide-loaded graphene oxide in step S2 is 80-100 ml: 2-3 g; S3: In a nitrogen atmosphere, pentaerythritol, PLLA, isophorone diisocyanate, dibutyltin dilaurate and N,N-dimethylformamide are mixed, reacted for 2-3 hours, and then functionalized graphene oxide is added to react for 8-10 hours, dried, and crushed to obtain functionalized polylactic acid; The usage ratio of pentaerythritol, PLLA, isophorone diisocyanate, dibutyltin dilaurate, N,N-dimethylformamide and functionalized graphene oxide in step S3 is 4.25-5g:5-10g:2-3g:0.01-0.05g:40-60ml:1-2g.
2. The antibacterial plastic according to claim 1, characterized in that: The weight average molecular weight of the polylactic acid is 60,000-150,000.
3. The antibacterial plastic according to claim 1, characterized in that: The plasticizer is a mixture of polyethylene glycol and chitosan solution in a weight ratio of 5:
3.
4. The antibacterial plastic according to claim 1, characterized in that: The antioxidant is one of N,N'-di-(1-methylheptyl)-p-phenylenediamine, 2,2,4-trimethyl-1,2-dihydroquinoline and 2,6-di-tert-butyl-4-methylphenol.
5. The antibacterial plastic according to claim 1, characterized in that: The graphene oxide in step S1 is in the form of a single-layer sheet or a layered structure of a small number of stacked sheets.
6. A method for preparing the antibacterial plastic according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: (1) Polylactic acid, functionalized polylactic acid and antioxidant are mixed evenly, extruded into a masterbatch by an extruder, and cooled and pelletized; (2) Add the masterbatch into an extruder, then add a plasticizer, and control the temperature of the extruder between 140-240°C to obtain composite particles; (3) The composite particles are blow-molded and packaged to obtain antibacterial plastics.
7. An application of the antibacterial plastic according to any one of claims 1 to 5, characterized in that: Used for moisture-proof food packaging.
Citation Information
Patent Citations
Biodegradable antibacterial plastic master batch, preparation method thereof and antibacterial plastic product containing biodegradable antibacterial plastic master batch
CN115418051A
Preparation method of polylactic acid antibacterial plastic
CN116622205A